Toxicity Effect of Some Insecticides on Spiders and Coccinellids in Brinjal and Cabbage Ecosystem - Dhamala, Sakil; Patra, Sandip; Thakuria, Dwipendra; Baiswar, Pankaj; Devi, M. Prabha; Ningthoujam, Kennedy (Indian Journal of Hill Farming, 2018)
To determine the effect of insecticides on natural enemies namely spiders and coccinellids in crop ecosystems, two field experiments were conducted at Entomology Research Farm, ICAR Research Complex for North Eastern Hill Region, Umiam, Meghalaya during kharif- 2016 on brinjal and rabi-2017 on cabbage. The experiments were laid out in randomized block design (RBD) with three replications for each treatment. Brinjal and cabbage seedlings (30days old) were transplanted in the plot size of 3m x 3m. Three insecticides viz. indoxacarb 14.5SC (75 and 150 g a.i./ha), chlorfenapyr 10SC (100 and 200 g a.i./ha) and chlorpyrifos 20EC (200 and 400 g a.i./ha) were applied with initiation of pest infestation along with control check. Spiders and coccinellids population were recorded from randomly selected 5 tagged plants/ plot before spray and subsequently 7 and 14 days after each spray for both the crops. Results revealed that there was a negative impact of chlorfenapyr and chlorpyrifos on spider population in brinjal and cabbage ecosystems. In brinjal, the lowest mean spider population was recorded in chlorpyrifos at higher doses (400 g a.i./ha) with 2.51 spiders/5plants followed by same insecticide at recommended dose (200 g a.i./ha) with 2.74 spiders/5plants and chlorfenapyr @200ga.i./ha (2.94 spiders/5plants) and chlorfenapyr @100 g a.i./ha (5.02spiders/5plants). The highest percentage reduction of coccinellids was also found in higher dose of chlorpyrifos (78.65%) followed by chlorpyrifos at recommended dose (75.44%), and higher dose of chlorfenapyr (32.74%) in brinjal. In cabbage, the similar trend of impact of insecticides on both spiders and coccinellids were observed.